Synthesis and Evaluation of Antimicrobial Activity of MetalComplexes of 4-(2’-Hydroxy Phenyl Imino) Phenyl Sulphonamide: Synthesis of metal complexes of 4-(2’-Hydroxy phenyl imino) phenyl sulphonamide - Bharat Bhusan Subudhi; Prasanna Kumar Panda; Sabuj Sahoo (Iranian Journal of Pharmaceutical Sciences, 2007)
Keeping in view the promising potential of carbonic anhydrase inhibitor based antimicrobials and enhancement of carbonic anhydrase inhibitory activity by metal complexes of sulfonamides, with an aim to develop better antimicrobial agents we have attempted investigation of antimicrobial activity of metal complexes of 4-(2’-hydroxy phenyl imino) phenyl sulphonamide. Sulfanilamide was taken as the starting material to synthesize 4-(2’-hydroxy phenyl imino) phenyl sulphonamide.Cu (II), Zn (II), Co (II), Ni (II) and Pb (II) complexes were synthesized following reported methods. The in vitroscreening was carried out using two gram positive bacteria (S. aureus, E. faecalis) and two gram-negative bacteria (E. coli, P.aeruginosa) by disc diffusion method. Metal complexes were found to enhance the antimicrobial potental of the ligand.